Comparison of Healthcare Experiences in Autistic and Non-Autistic Adults: A Cross-Sectional Online Survey Facilitated by an Academic-Community Partnership - Nicolaidis, Christina (Springer-Verlag, 2012)
BACKGROUND: Little is known about the healthcare experiences of adults on the autism spectrum. Moreover, autistic adults have rarely been included as partners in autism research. OBJECTIVE: To compare the healthcare experiences of autistic and non-autistic adults via an online survey. METHODS: We used a community-based participatory research (CBPR) approach to adapt survey instruments to be accessible to autistic adults and to conduct an online cross-sectional survey. We assessed preliminary psychometric data on the adapted scales. We used multivariate analyses to compare healthcare experiences of autistic and non-autistic participants. RESULTS: Four hundred and thirty-seven participants completed the survey (209 autistic, 228 non-autistic). All adapted scales had good to excellent internal consistency reliability (alpha 0.82–0.92) and strong construct validity. In multivariate analyses, after adjustment for demographic characteristics, health insurance, and overall health status, autistic adults reported lower satisfaction with patient-provider communication (beta coefficient −1.9, CI −2.9 to −0.9), general healthcare self-efficacy (beta coefficient −11.9, CI −14.0 to −8.6), and chronic condition self-efficacy (beta coefficient −4.5, CI −7.5 to −1.6); higher odds of unmet healthcare needs related to physical health (OR 1.9 CI 1.1–3.4), mental health (OR 2.2, CI 1.3–3.7), and prescription medications (OR 2.8, CI 2.2–7.5); lower self-reported rates of tetanus vaccination (OR 0.5, CI 0.3–0.9) and Papanicolaou smears (OR 0.5, CI 0.2–0.9); and greater odds of using the emergency department (OR 2.1, CI 1.8–3.8). CONCLUSION: A CBPR approach may facilitate the inclusion of people with disabilities in research by increasing researchers’ ability to create accessible data collection instruments. Autistic adults who use the Internet report experiencing significant healthcare disparities. Efforts are needed to improve the healthcare of autistic individuals, including individuals who may be potentially perceived as having fewer disability-related needs.